Is inflation persistence in Nepal substantially imported and influenced by shocks? - Pokhrel, Aditya (Economic Review of Nepal, 2025)
This study examines the inflation persistence in Nepal, stating whether macroeconomic shocks and the external drivers affect the persistence and the channels. Prior studies discuss imported inflation and the domestic transmission, but do not address evidences that how persistence changes after the shocks across the consumer price index (CPI) breakdown components. To address the gap, this study employed a dynamic framework. This study also modeled the shock regimes and examined the external influences. This study employed autoregressive (AR) models with shock interactions and local projections, using an instrument variable (IV), using the Reserve Bank of India’s (RBI) repo rate as an external shift (lever) for Nepal’s policy rate, which is further supported by placebo tests. This study revealed that the food inflation has a moderate and non-explosive persistence, whereas the non-food is mean-reverting. Earthquake (2015) raises the persistence of food inflation, but COVID reduces the persistence of headline inflation. The effect of Indian inflation is substantial, and the shocks from the policy rate (India) affect temporarily, which indicates the inflation persistence (Nepal) is component-specific and partly imported.